Case report: Ketogenic diet acutely improves cognitive function in patient with Down syndrome and Alzheimer’s disease - Bosworth, Annette; Loh, Vyvyane; Stranahan, Blackjack N.; Palmer, Christopher M. (Frontiers in Psychiatry, 2023)
Ketogenic diets have a century-long history as a therapeutic tool to treat intractable epilepsy. Recently, a renewed interest in neuroketotherapeutics has arisen, with ketogenic diets being explored for the treatment of neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease, as well as mental health conditions. Herein, we present a case report of a 47-year-old woman with Down syndrome diagnosed with Alzheimer’s disease and absence seizures with accelerated cognitive decline over 6 years. A ketogenic diet restored her cognitive function over 6 weeks, with an increase in Activities of Daily Living Scale score from 34 to 58. A therapeutic ketogenic diet was associated with significant cognitive improvement in this patient with concurrent Down syndrome and dementia.